2017
DOI: 10.1177/1553350617715162
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Streaming Video System With a Point-of-View Head Camera Transmission of Surgeries to Smartphones and Tablets: An Educational Utility

Abstract: This study presents a local streaming video system of live surgeries to smartphones and tablets and shows its educational utility, low cost, and simple usage, which offers convenience and satisfactory image resolution, thus being potentially applicable in surgical teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The studies demonstrated that microlearning can improve performance and potentially increase safety in the clinical environment [29,30]. This potential is consistent with a wide range of previous research on microlearning and medical training [14,16] and continuing education in nursing [13,15]. Results from previous studies along with our findings highlighted how microlearning could be used as a refresher before performing skills that are infrequently used or when performing new skills without previous experience.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The studies demonstrated that microlearning can improve performance and potentially increase safety in the clinical environment [29,30]. This potential is consistent with a wide range of previous research on microlearning and medical training [14,16] and continuing education in nursing [13,15]. Results from previous studies along with our findings highlighted how microlearning could be used as a refresher before performing skills that are infrequently used or when performing new skills without previous experience.…”
Section: Discussionsupporting
confidence: 89%
“…This is particularly important in health professions education, which changes constantly with advancements in medicine and health care delivery systems [12]. The effectiveness of microlearning for health care professionals has been reported in clinical studies, such as a mobile app for recording learning experiences in nursing practice [13]; an interactive case-based teaching session in medical training programs [14]; a mobile gaming device that promotes nursing research knowledge, attitudes, and practice [15]; and a streaming video system with point-of-view camera transmission of surgeries to students’ smartphones and tablets [16]. As such, microlearning has been endorsed by many health professions educators, programs, and organizations as a means of facilitating student learning, training, and continuing education [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It also allows image sharing, which can be used for streaming video transmission of surgeries to other smartphones and tablets, for educational purposes. 22 However, if the internet quality is poor, it can limit the usefulness of these devices.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The authors concluded that NEST was a reliable and affordable learning tool. 30 Chaves et al 35 evaluated the effectiveness of a telementoring programme whereby gynaecology residents and medical students received education on their smartphones connected to a wireless network though live surgery. 35 94% reported that the streaming video system was an effective educational tool.…”
Section: Resultsmentioning
confidence: 99%